Moderatisme Politik Islam Indonesia Era Soekarno: Studi Resolusi konflik Indonesia – Malaysia - Sri Windari; Muhammad Ilham Aziz (UIN Sunan Gunung Djati Bandung, 2022)
This paper examines the agreement between Indonesia and Malaysia which is a form of moderate Islamic attitude shown by the parties or community organizations that played a role at that time. In this study, the authors used a qualitative descriptive research method. The data analysis technique used is the technique proposed by Miles and Huberman, which consists of data reduction, data presentation, and conclusions. The resolution of the conflict that occurred between Indonesia and Malaysia is also known as Konfrontasi or